Effect of Dietary Supplementation of Prebiotic and Acidifier Powder on Growth Performance and Haemato-biochemical Parameters in Broilers - Rajoriya, Harendra Singh; Shende, Kavita A.; Chavhan, Dinesh M.; Meel, Mahendra Singh; Joshi, Monika (International Journal of Bio-resource and Stress Management, 2024)
This study was undertaken during September–October, 2023 at the Department of Animal Nutrition, C.V.A.S, navania, Udaipur, Rajasthan University of Veterinary and Animal Sciences, Bikaner, Rajasthan, India to evaluate the effect of supplementation of prebiotics (Fructooligosaccharide) and acidifier either singly or in combination, on performance of broilers. The feeding trial was conducted on one hundred and twenty days-old broiler chicks randomly divided into three equal groups viz. C, T1, T2 and T3 comprised 30 birds each, at Poultry Unit in Livestock Farm Complex. Group C served as control and received a standard broiler mash. The birds in group T1 were fed standard broiler mash+prebiotic @ 0.5% of feed from 0–3 weeks and standard broiler mash+prebiotic @ 0.25% of feed from 4–6 weeks, T2 were fed standard broiler mash+acidifier @ 0.5% of feed from 0–3 weeks and standard broiler mash+acidifier @ 0.25% of feed from 4–6 weeks and T3 were fed standard broiler mash+prebiotic+acidifier @ 0.5% (1:1) of feed from 0–3 weeks and standard broiler mash+prebiotic+acidifier @ 0.25% (1:1) of feed from 4–6 weeks. The results showed that the body weight, body weight gain, daily body weight gain, average feed intake, feed conversion ratio, Hb, PCV, serum protein, cholesterol and RBC were highly significant (p<0.01) in T3 group as compared to control group. In conclusion, the addition of FOS, Acidifier and combination of FOS with acidifier in the diet of broiler chickens improve various growth performance and hemato-biochemical parameters.